Antigen-presenting cell internalization is key for understanding and evaluating therapeutic antibodies’ immunogenicity - Lteif, Maria; Pallardy, Marc; Turbica, Isabelle (Frontiers in Immunology, 2025)
Therapeutic antibodies have revolutionized the treatment of many diseases. However, their safety and efficacy are often altered by their immunogenicity, as many patients frequently develop anti-drug antibodies. Dendritic cells (DCs) are the most potent antigen-presenting cells of the immune system. DCs initiate the immunogenic adaptive immune response by internalizing therapeutic antibodies using different pathways and receptors, leading to antigen presentation to T-cells. Recently, studies have shown that the uptake of antibodies by immune cells could contribute to their immunogenicity. This review will present in detail the different DC internalization mechanisms and then discuss the impact of therapeutic antibodies’ properties and aggregation on their uptake by DCs and, therefore, their immunogenicity. We will also highlight cellular models and strategies used to evaluate antibodies’ internalization. Addressing the uptake of antibodies by DCs could help to predict the risk of immunogenicity and to develop mitigation strategies.